Versatile and Tunable Poly(Ethylene Glycol)-Based Hydrogels Crosslinked through the Ugi Reaction - Padrão, Inês (2022)
This work was supported by the Applied Molecular Bioscience Unit – UCIBIO (UIDB/04378/2020); projects PTDC/BII‐BIO/28878/2017 (LISBOA‐01‐0145‐FEDER‐028878); PTDC/SAL‐SER/30388/2017 (POCI‐01‐0145‐FEDER‐030388); Ph.D. fellowships to CF (PD/BD/105871/2014); CE (SFRH/BD/113112/2015). The authors are grateful to Prof. Ana Rita C. Duarte from Associate Laboratory for Green Chemistry – LAQV, Faculdade de Ciências e Tecnologia, Universidade Nova de Lisboa for facilitating the rheology studies.